Կնոջ դերի ընկալումը ամուսնական յարաբերութիւնների համապատկերում (Պատմական համառօտ ակնարկ) - Դալլաքեան, Լիանա (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В статье обобщены изменения роли женщин в контексте семейно-брачных отношений. Изначально, в брачных отношениях женщины занимали довольно низкую позицию. В языческую эпоху господствовало многоженство. Однако после принятия христианства ситуация полностью изменилась. The article summarizes the changes in the role of women in the context of marital relations. It is well-known that initially women held a rather low position in marriage. In pagan times, polygamy was a widespread phenomenon. However, after the adoption of Christianity the situation completely changed.
Keywords: The family; Marriage; Woman; History